EMPOWERMENT OF DOLLY LOCALIZATION COMMUNITIES WITH BATIK-BASED INNOVATION AND EXPORT POTENTIALS IN PUTAT JAYA AREA, SURABAYA EAST JAVA - Widiana, Muslichah Erma; Wahyudi, Suhud; Enny W., Mahmuda (Advances in Social Sciences Research Journal, 2020)
Community service program entitled Innovation of Batik Craftsmen by Empowering Human Resources "Ex-Dolly Localization" Based on High Competitiveness Science and Technology and Leading Export Potentials of Kel. Putat jaya barat, Surabaya East Java. Partners (1) Mrs. Kusmiati Putat Jaya Barat VIIIB-31 Surabaya. Partners (2) The Women of Putat Jaya Barat VIIIB and surrounding areas who have an interest as batik artisans. Partners are assisted by the City Government which is affected by the closure of the localization of the economy, then the City Government facilitated the establishment of the Jarak Arum. Problems: 1) The batik cloth produced starts from a monotonous design, so far it has been designed conventionally so it is not effective. 2) tools for stamped batik cloth have often been used so that the design does not vary. 3) The craftsmen to always be enthusiastic need to be motivated as craftsmen and so batik that is competitive and has a high selling value needs to be widely known. The solution: 1) Technology Application of the software for batik design and coloring so that new designs will always appear. 2) Stamped batik equipment consisting of a stamp and its stamp 3) Knowledge of entrepreneurial spirit and technology in conducting marketing activities. Methods: (1) Design, build, maintain the use of Technology Application of software for batik design and coloring so that new designs will always appear (2) Design, build, maintain the use of stamp equipment for partners1 and partners2 (3) Training, practice, and assistance transmits entrepreneurial mindset and behavior, e-marketing with smartphones for partners 1 and partners 2.